Pappaseng values: A cultural framework for national character development - Fadli; Wati, Fitra Widya; Irvan Tasnur; Boontra, Molraphaporn (AL MA'ARIEF : Jurnal Pendidikan Sosial dan Budaya, 2025)
Pappaseng, a form of traditional Bugis oral literature, serves as a cultural medium for transmitting moral values through proverbs, advice, songs, and dialogic expressions. These forms function as pedagogical tools for both individual and communal character development. This study aims to explore the potential of Pappaseng as a culturally rooted framework for national character education in Indonesia. Employing a qualitative descriptive method through library research, the analysis draws upon primary Pappaseng texts and secondary sources from anthropology, education, and local wisdom studies. The research addresses the limited integration of indigenous oral traditions within current character education models. The findings reveal that Pappaseng embodies essential values, such as honesty (lempu’), wisdom (amaccang), and courage (getteng), that can be meaningfully integrated into educational practices to promote ethical awareness and national identity. These values are transmitted not only through interpersonal advice but also via traditional artistic expressions, including kaddo bora (songs) and dialogic storytelling. This study offers a novel contribution by positioning Pappaseng as an underutilized indigenous epistemology within the discourse on character education. As such, it provides a culturally relevant resource for strengthening national character through formal education and community engagement initiatives.